Shǐxīng, a Sino-Tibetan language of South-West China: a grammatical sketch with two appended texts - Chirkova, Katia (2024)
This article is a brief grammatical sketch of Shǐxīng, accompanied by two analyzed and annotated texts. Shǐxīng is a little studied Sino-Tibetan language of South-West China, currently classified as belonging to the Qiangic subgroup of the Sino-Tibetan language family. Based on newly collected data, this grammatical sketch is deemed as an enlarged and elaborated version of Huáng & Rénzēng’s (1991) outline of Shǐxīng, with an aim to put forward a new description of Shǐxīng in a language that makes it accessible also to a non-Chinese speaking audience.